Thermal analysis and electrochemical study of Hg reactions on Pt-30% Ir alloy electrode - Milare, E.; Turquetti, J. R.; Souza, G. R.; Benedetti, Assis Vicente [UNESP]; Fertonani, F. L. (Springer, 2006)
Thermogravimetry (TG), cyclic voltammetry (CV) and other analytical techniques were used to study the reactions of mercury with Pt-30% Ir alloy. The results allowed to suggest that an electrodeposited mercury film interacts with the substrate and when subjected to heat or electrochemical removal at least four mass loss steps or five peaks appeared during the mercury desorption process. The first two steps were attributed to Hg(0) removal probably from the bulk and from the adsorbed monolayer which wets the electrode surface. These two processes are responsible for peaks D and F in the cyclic voltammograms. The last two peaks (G, H) in CV were ascribed to the intermetallic compound decomposition. In TG curves, the last two steps were attributed to the PtHg4 (third step), and PtHg2 decomposition followed by Hg removal from the subsurface. The PtHg2 was formed by an eutectoide reaction: PtHg -> PtHg2+Hg(Pt-Ir). The Hg diffused to the subsurface was not detectable by cyclic voltammetry.
Keywords: alloy; cyclic voltammetry; SXR; thermogravimetry